The relationship between sleep quality and occupational fatigue in endoscopy nurses: mediating role of positive coping style - Zeng, Zhi; Zhou, Sumei; Xie, Guiqiong; He, Yazhi; Ling, Jing (Frontiers in Public Health, 2024)
Nursing occupational fatigue has emerged as a critical issue affecting the safety and health of nurses. This phenomenon not only impairs nurses' performance and mental well-being but also poses risks to patient safety and the quality of care provided. This study focuses on endoscopic nurses to explore the mediating role of positive coping styles between sleep quality and occupational fatigue, aiming to identify effective strategies to alleviate fatigue, thereby improving the work environment and enhancing healthcare quality. Methods From July to August 2023, a cross-sectional design was used to select 258 endoscopy nurses from 25 top-three hospitals in 14 cities across 5 provinces in China. Data was collected through general information questionnaires, Fatigue assessment instrument, Pittsburgh sleep quality index, and Simple Coping Style Questionnaire.A structural equation model of sleep quality -positive coping style -occupational fatigue was constructed using Amos 26.0, and Bootstrap was employed to test the mediating effect. Results The results showed that the mean scores of sleep quality, occupational fatigue, and positive coping style for endoscopy nurses were 8.89±4.13, 17.73±5.64, and 18.32±10.46, respectively. Positive coping style were negatively correlated with sleep quality and occupational fatigue (P＜0.001). Positive coping style partially mediated the relationship between sleep quality and occupational fatigue, with a mediating effect value of 0.253, accounting for 42.10% of the total effect.Conclusion Sleep quality can indirectly affect the level of occupational fatigue through positive coping style.Nursing managers should enhance nurses' positive coping skills, improve nurses' sleep quality, and reduce occupational fatigue among nurses.